Exploring the Channels of Financial Inclusion’s Impact on Poverty Reduction in Sub-Saharan Africa - Musa Abdullahi Sakanko; Nurudeen Abu; Awadh Ahmed Mohammed Gamal; Salimatu Rufai Mohammed (Scientific Annals of Economics and Business, 2025)
There is no doubt that Sub-Saharan Africa (SSA) is home to many financially excluded persons, and the sub-region accounts for a high proportion of the world’s poor. Despite the co-existence of low level of financial inclusion (FI) and high poverty level in SSA, little attention has been given to empirical linkage between these two phenomena. This research attempts to unravel the channels through which FI (measured by the composite financial inclusion index developed using the Principal Component Analysis) impact poverty reduction in a sample of 25 SSA countries. The system-Generalized Method of Moments (i.e., system-GMM) estimator was employed to analyze data for the 2004-2022 period. The empirical outcomes portray that the FI-poverty reduction relation is non-linear, and it identify income growth, consumption expenditure, agricultural output, and unemployment as the channels through which FI influences poverty reduction in the SSA region. The findings further reveal that an FI value beyond thresholds of 1.44 and 5.25 increases income growth and reduces unemployment, thereby reducing poverty. Additionally, an FI value below thresholds of 2.87 and 1.40 positively impacts consumption expenditure and agricultural output, leading to poverty reduction. The study recommends that the monetary authorities in SSA adopt policies which increase the access to financial services and promote financial literacy to enhance financial inclusion and reduce poverty.